Impacto da mobilização passiva na microcirculação e na circulação sistêmica em pacientes com choque séptico - Pinheiro, Tuanny Teixeira [UNIFESP] (2017)
Objective: To evaluate, in patients with septic shock, the impact of passive mobilization in the sublingual microcirculation, in the systemic hemodynamics and tissue perfusion variables. Method: This is a clinical trial in patients older than 18 years, with septic shock and norepinephrine at doses between 0.1 and 1.0 mcg/kg/min, sedated with a Ramsay Scale of 6 and with invasive mechanical ventilation after initial resuscitation phase. We excluded patients with intracranial hypertension, in status epilepticus, with cardiac arrhythmia at the time of the study, acute myocardial infarction (Killip 4), thrombocytopenia (< 30,000/μL), hemoglobin < 7.0 g/dL, leukocytosis (> 50,000/μL), peripheral arterial disease, worsening oxygenation status in the last 6 hours (oxygen partial pressure to inspired oxygen fraction decrease > 50), circulatory shock of multiple causes, pregnancy, clinical conditions with contraindication for the mobilization or microcirculation sampling, moribund patients and those who died before the exercise session. Passive exercise was applied for 20 minutes, 5 minutes in each member with 30 repetitions per minute. Hemodynamic, laboratory and microcirculatory variables were compared before (T0) and up to 10 minutes after passive movement (T1). The microcirculation was assessed using the sidestream dark field. Continuous variables were described as mean and standard deviation or median and interquartile 25-75% using paired Student's t test or paired Wilcoxon test hen appropriate. We compared the microcirculatory variables at moments T0 and T1 in the low-dose noradrenaline group (< 0.3 mcg/kg/min) and the high-dose noradrenaline group (≥ 0.3 mcg/kg/min) using t-paired test or Wilcoxon paired test, as appropriate. We also compared the microcirculatory variables variation between T0 and T1 between the groups, using t-test or Mann-Whitney test, as appropriate. We correlated potential variations in microcirculation with the variation of heart rate (HR), cardiac index (CI) and mean arterial pressure (MAP), using the Spearman test. We also compared individuals with and without improvement in microcirculation variables in relation to HR, CI and MAP variation using the Mann Whitney test. In all tests, we used level of significance value of p < 0.05. Results: Thirty-five patients were included, being 45.7% male, with a median age of 68 (49.0 - 78.0) years, mean SAPS 3 score of 66.7 ± 12.1 and median SOFA score of 9 (7.0 - 12.0). After passive mobilization, there was a slight but significant increase in PPV (T0: 78.2 (70.9 - 81.9); T1: 80.0 (75.2 - 85.1), p < 0.029), without any change in other microcirculation variables. The increase in PPV was significant only in the high-dose noradrenaline group, but the PPV variation (T1-T0) was not statistically different between the two groups. We could not find any other significant differences between the low-dose and high-dose groups. There was a reduction in HR (T0: 95.6 ± 22.0; T1: 93.8 ± 22.0, p < 0.040) and body temperature (T0: 36.9 ± 1.1; T1: 36.7 ± 1.2, p < 0.002), but without clinical relevance. There was no change in other hemodynamic parameters and lactate and central venous oxygen saturation levels. There was no significant correlation between PPV variation and HR variation (r = -0,010, p = 0,955), CI (r = 0,218, p = 0,215) and MAP (r = 0,276, p = 0,109). However, individuals who improve PPV has smaller variation in MAP [1.0 (- 1.0 to 4.0)] with passive mobilization than those without improvement in PPV [- 2.5 (- 7.25 - 0.25)], p = 0.05. Conclusion: In patients with septic shock after the initial phase of hemodynamic resuscitation, passive exercise seems to be associated with increased proportion of perfused vessels in the sublingual microcirculation and doesn’t compromise the systemic hemodynamics or tissue perfusion variables. This alteration in the proportion of perfused vessels was associated with a smaller reduction in the systemic arterial blood pressure after passive exercise.